Exploring the associations between arterial stiffness and spinal cord impairment: A cross-sectional study. (September 2014) - Miyatani, Masae; Szeto, Maggie; Moore, Cameron; Oh, Paul I.; McGillivray, Colleen F.; Catharine Craven, B.
Abstract : Background/Objective: Elevated aortic arterial stiffness (aortic pulse wave velocity: aPWV) is an independent coronary artery disease predictor among the general population. The purpose of this study was to: (1) report aPWV values in a representative cohort of patients with spinal cord injury (SCI); (2) to compare aPWV values in people with SCI based on neurological level of injury; and (3) to contrast the reported aPWV values with available normal values for the general population. Methods: Adults with chronic SCI ( n = 87) were divided into two groups (TETRA group, n = 37 and PARA group, n = 50). aPWV and potential confounders of aPWV were assessed. Analysis of covariance was used for comparisons between groups and adjusted for the confounders. Subjects' aPWV values were contrasted with reference values for general population determined by "The Reference value for arterial stiffness' collaboration" and prevalence of abnormal aPWV defined as greater than or equal to the age-specific 90th percentile was reported. Results: Prevalence of abnormal aPWV in the cohort was 25.3%. After adjusting for covariates, the mean aPWV values were significantly different between two groups (TETRA: 8.0 (95% confidence interval (CI): 7.5–8.6) m/second, PARA: 9.0 (95% CI: 8.5–9.4) m/second, P = 0.010). The prevalence of abnormal aPWV was significantly higher in the PARA group (36%) compared to the TETRA group (11%) (P = 0.012). Conclusions: One-quarter of the total cohort had an abnormal aPWV. Subjects with paraplegia had higher aPWV values and a higher frequency of abnormal aPWV than subjects with tetraplegia. Elevated aPWV in people with SCI, particularly those with paraplegia, may impart significant adverse cardiovascular consequences.